PENGARUH KEPUASAN DAN WORD OF MOUTH TERHADAP LOYALITAS KONSUMEN PADA GREEN PRODUCT MEREK ORIFLAME DI KOTA DENPASAR - Ni Made Dewi Kansa Putri (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
Consumers who are increasingly critical of global issues are primarily concerned with the environment, encouraging producers to market environmentally-based products. one of them through the use of the label "back to nature" in the cosmetics industry. Changing this environment-based marketing concept, requires the right marketing strategy to create customer satisfaction and loyalty. Retained customers will be happy to reveal positive things and provide recommendations about the product to others (word of mouth). This research was conducted on consumer in denpasar city by using data of number of consultant oriflame counted 100 people. Data were analyzed by path analysis technique, where validity and reliability were tested in the early stages of testing. The result of analysis shows that satisfaction and word of mouth have significant influence to consumer loyalty on oriflame brand green product.The results of this study recommend the formulation of environment-based product marketing strategy so that it can win the competition is increasingly tight and competitive.